Detailed experimental investigation of the spatially distributed gas release and bed temperatures in fixed-bed biomass combustion with low oxygen concentration. (October 2020) - Archan, Georg; Anca-Couce, Andrés; Gregorc, Jurij; Buchmayr, Markus; Hochenauer, Christoph; Gruber, Johann; Scharler, Robert
Abstract: This publication focuses on the experimental investigation of a novel small-scale fuel flexible biomass combustion technology with a fixed-bed employing a low oxygen concentration. It was obtained through a low primary air ratio and the additional supply of recirculated flue gas. The plant was operated with spruce wood chips, which contained three different mass fractions of water, and miscanthus pellets. All relevant components of the released gas above the fixed-bed were measured, as well as the 3D bed temperature distribution. The balances confirmed a high experimental data consistency. Therefore, it was possible to determine the location of the four different conversion zones inside the fixed-bed: drying, pyrolysis, char gasification and char oxidation. The reduction of CO2 to CO in the char reduction zone worked efficiently across the entire grate area. Furthermore, the results showed that the water mass fraction of the fuel did not influence the dry product gas composition, but significantly affected the location for the release of pyrolysis products such as tars. It was found that the low oxygen concentration in the fixed-bed combined with flue gas recirculation was an effective method to reduce bed temperatures and therefore its inorganic emissions while significantly increasing feedstock flexibility. The investigations provided fundamental findings on the conversion and release behavior of the new technology under real operating conditions and are very useful for further experimental work and CFD simulations targeting the reduction of PM and NOX emissions. Highlights: Development of fuel flexible biomass combustion technology with low emissions. Detailed investigation and characterization of fuel conversion and release behavior. Compact bed design with low temperatures and high content of tar in released gas. Supply of recirculated flue gas below the grate leads to high fuel flexibility. Data consistency checked by mass and energy balance calculation.